2021
DOI: 10.1016/j.invent.2021.100425
|View full text |Cite
|
Sign up to set email alerts
|

Technology and psychotherapeutic interventions: Bibliometric analysis of the past four decades

Abstract: Background Rapid growth of the integration of technology and psychotherapeutic interventions has been noted, but no clear quantification of this growth has been done. Aims This bibliometric analysis seeks to quantify the growth, trends, and applications of technology in psychotherapeutic interventions over the last 40 years. Methods Searches were conducted in the Web of Science (WOS) database for all existing technology-psychotherapy-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Ten of the 27 excluded studies either tried to predict the outcome of cognitive behavior therapy by using natural language processing, or tried to predict optimal therapeutic interventions with sociodemographic data ( 30 40 ). Another 16 studies excluded were reviews about machine learning and its utilization within psychotherapy, psychopharmacotherapy, and diagnostics ( 19 , 27 , 38 , 41 51 ). Another 8 Studies were excluded because they treated patients with psychotherapy, yet did not specify which kind of treatment approach they used ( 22 , 29 , 52 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ten of the 27 excluded studies either tried to predict the outcome of cognitive behavior therapy by using natural language processing, or tried to predict optimal therapeutic interventions with sociodemographic data ( 30 40 ). Another 16 studies excluded were reviews about machine learning and its utilization within psychotherapy, psychopharmacotherapy, and diagnostics ( 19 , 27 , 38 , 41 51 ). Another 8 Studies were excluded because they treated patients with psychotherapy, yet did not specify which kind of treatment approach they used ( 22 , 29 , 52 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…A distinctive increase in research productivity, though, was observed early on in 2020 with the beginning of the COVID-19 pandemic, which was followed by a surge in publications reporting on preventive digital mental health interventions, reflecting the fast-track submission processes that were adopted by academic journals to speed up knowledge dissemination. The Journal of Medical Internet Research was the leading and most influential source of publications, which also ranked first in a previous bibliometric analysis of research production in technology and psychotherapeutic interventions [ 50 ]. JMIR Formative Research ranked second, further highlighting the surge in interest in developing and, thus, piloting and evaluating novel interventions during the last three years.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotherapy for depression can be offered in different settings and treatment modalities. Traditionally, treatment is delivered face to face, but internet-based therapy (IBT) has gained popularity and the number of randomized clinical trials (RCTs) of IBT has grown during the past 2 decades . Recent direct and indirect comparisons suggest that therapist-guided IBT can be as beneficial as face-to-face therapy (FTF).…”
Section: Introductionmentioning
confidence: 99%